Growth of Shorea Leprosula Seedlings Prepared in Combo Nursery Technique to Support Mine Reclamation - Febrian , Febrian Ari Nugroho; Irdika, Irdika Mansur; Arum , Arum Sekar Wulandari (Jurnal Wasian, 2021)
Combo nursery technique is a technique where seedlings/cuttings of Shorea leprosula, Gliricidia sepium, and Brachiaria decumbens grass were planted in one polybag to support mining reclamation. To reduce competition effects among the three species, optimum media and size of polybag need to be investigated. The objective of this experiment is to analyse the effect of size of polybag and media composition on the growth of S. leprosula, G. sepium, and B. decumbens grass in the combo nursery technique. The experiment used Randomised Complete Design in Factorial with two factors, i.e. media compositions (soil : compost (2 : 1, v/v), (1 : 1, v/v), (1 : 2, v/v), and soil : compost : rice husk (7:3:1, v/v/v); and size of polybag (15 x 20 cm, 20 x 20 cm, dan 25 x 25 cm). Each treatment had four replications, and each replication consisted of four polybags. The results showed no significant interaction effects between the composition of media and the size of polybag; however, media compositions of soil: compost (1:1) and (1:2), and the sizes of polybag 20 x 20 cm and 25 x 25 cm significantly eliminated competition and significantly increased the growth of S. leprosula and the number of tiller of B. decumbens grass.